KEMAMPUAN ADSORBEN LIMBAH LATEKS KARET ALAM TERHADAP MINYAK PELUMAS DALAM AIR - Edward Tandy, Ismail Fahmi Hasibuan, Hamidah Harahap (Universitas Sumatera Utara, 2012)
Natural rubber latex waste usually throw away to be unused materials and caused environment issue. One of the ways to handle this environment issue by using natural rubber latex waste as oil adsorbent. Natural rubber latex waste also had oleophilic and hydrophobic properties that are suitable to being used as oil adsorbent. In this research, researchers found out adsorption capacity of natural rubber latex waste to oil and oil from water, also the characteristics of it’s adsorption with Langmuir and Freundlich isoterm adsorption model. The adsorption characteristics of lubricant oil from water with natural rubber latex waste more fitted well with Langmuir isotherm equation model and the maximum adsorption ability of lubricant oil from water with natural rubber latex waste also significantly increased with the contact time till reached the equilibrium. The results of this study concluded that natural rubber latex waste had a great adsorption capacity and suitabled for being used as oil adsorbent.Keywords : natural rubber latex waste, oil in water, adsorption, adsorption equilibrium, oil adsorbent